The Islamic finance as an alternative to the small and medium enterprises - iyache, zoubire (Milev Journal of Research and Studies, 2016)
This study aims to highlight the role of Islamic finance in resolving the problem of financing small and medium enterprises in order to ensure their continuity and their development, especially in light of what these enterprises suffer of financing obstacles. The study shows that Islamic finance would contribute to the development of small and medium enterprises and to reduce its financing problems, through the several modes characterized by flexibility, integration and diversity, which contributes to the provision of financial resources, according to the line with the financing needs for these enterprises